An Overview of Recent Electrochemical Immunosensing Strategies for Mycotoxins Detection. Issue 8 (15th July 2016) - Catanante, Gaelle; Rhouati, Amina; Hayat, Akhtar; Marty, Jean Louis
Abstract: Electrochemical immunosensors are affinity ligand based biosesnors based on solid state devices in which immunochemical reactions are coupled to a transducer surface to generate the output electrochemical signal. The concept of immunosensor methodology is similar to conventional ELISA based immunoassays; however, in contrast to immunoassays, modern transducer technology permits the highly sensitive quantification of the immune complex in divers ways. Mycotoxins are naturally occurring toxic secondary metabolites produced by fungi contaminating food and feed and are responsible for mycotoxicosis with symptoms of intoxication causing substantial effects on animal and human health. Based on the adverse effect, it has been very crucial to develop ultrasensitive sensing methodologies to ensure food safety and prevent risks in agro‐food and environmental sector. For these purposes, many electrochemical immunosensors based on different analyzing techniques have been reported for mycotoxins monitoring. In this review paper, we provided a general overview on the practical aspects of electrochemical imunosensor designs such as assay format, choice of the transducer surface, immobilization methodologies, signal generating probe and type of output electrochemical signal. In doing so, we also reviewed the recent development in electrochemical immunosensor applications for mycotoxin analysis. Abstract :